Factors Influencing Students Attitudes towards Learning English as a Foreign Language in Tertiary Institutions in Zanzibar, Tanzania - M, Musa (International Journal of Linguistics, 2023)
Purpose: This study aimed at investigating the factors influencing students' attitudes towards learning English as a foreign language in tertiary institutions in Zanzibar. Methodology: The study adopted a desktop methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The results revealed that there exist conceptual and contextual gaps relating to the study on the factors influencing students' attitudes towards learning English as a foreign language in tertiary institutions in Zanzibar, Tanzania. Preliminary empirical review reveals that these attitudinal factors are divided into two main domains, that is, internal and external factors. Internal factors included students' interest, self-confidence, lexicon knowledge, anxiety, risk-taking willingness, curiosity, and awareness of the English role. Unique Contribution to Theory, Practice and Policy: The Affective Filter hypothesis, Cognitive theory and the Social learning theory may be used to anchor future studies in the acquisition of second foreign language in tertiary institutions. The study will be beneficial to Foreign Language teachers in these tertiary institutions, the school administration and policymakers in establishing strategies that will create a conducive environment for learners to be able to adjust and easily comprehend the foreign language being delivered.